The racialized experiences of Asian American teachers in the US : applications of Asian critical race theory to resist marginalization - Kim, Jung, 1977-; Hsieh, Betina (New York : Routledge, 2022)
"Drawing on in-depth interviews, this text examines how Asian American teachers in the US have adapted, persisted, and resisted racial stereotyping and systematic marginalization throughout their educational and professional pathways. Utilizing critical perspectives combined with tenets of Asian Critical Race Theory, Kim and Hsieh structure their findings through chapters focused on issues relating to (anti-)essentialism, intersectionality, and the broader social and historical positioning of Asians in the US. Applying a critical theoretical lens to the study of Asian American teachers demonstrates the importance of this framework in understanding educators' experiences during schooling, training, and teaching, and in doing so, the book highlights the need to ensure visibility for a community so often overlooked as a "model minority", and yet one of the fastest growing racial groups in the US. This text will benefit researchers, academics, and educators with an interest in the sociology of education, multicultural education, and teachers and teacher education more broadly. Those specifically interested in Asian American history and the study of race and ethics within Asian studies will also benefit from this book. Jung Kim is Associate Professor of Literacy at Lewis University, USA Betina Hsieh is Associate Professor of Teacher Education at California State University-Long Beach, USA"--
Introduction: Framing the experiences of Asian American educators -- Asianization and educational experiences of racialization and marginalization -- Considering Asian American transnational contexts: Immigration, generations, and identities in education -- Re-Constructive history: Missing Asian American stories and voices in American curricula and classrooms -- Strategic anti-essentialism: Balancing ethnic identity and pan-ethnic solidarity -- Intersectionality and Asian American educators' experiences of oppression along multiple axes of their identities -- Commitment to justice: Conscientization and action -- Story, theory, and praxis: How our stories can change our classrooms.
Keywords: Asian American teachers; Critical race theory; EDUCATION / Multicultural Education; EDUCATION / Philosophy & Social Aspects; SOCIAL SCIENCE / Ethnic Studies / Asian American Studies